Transesterification of methylsulfate and ethylsulfate ionic liquids - an environmentally benign way to synthesize long-chain and functionalized alkylsulfate ionic liquids - Himmler, Simone; van Hal, Roy; Schulz, Peter; Wasserscheid, Peter; et al. (Green Chemistry, 2006)
A new environmentally friendly method to synthesize long-chain and functionalized alkylsulfate ionic liqs. is reported. The two-step synthesis comprises the synthesis of a methylsulfate or ethylsulfate ionic liq. by direct alkylation in the first step. In the second step, this intermediate is transformed in a transesterification reaction, using different functionalized and non-functionalized alcs., to the corresponding new alkylsulfate melts. The entire reaction sequence is halide-free and liberates methanol or ethanol as the only byproducts. Moreover, it is carried out in a solvent-free manner and scale-up is straight forward. [on SciFinder(R)]
Keywords: alkylsulfate ionic liq prepn